2004
DOI: 10.1210/jc.2003-031977
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Remnants and Endothelial Dysfunction in the Postprandial Phase

Abstract: The objective of this work was to study whether changes in remnant lipoprotein (RLP) plasma levels during the postprandial phase relate to alterations of the endothelial function. Fasted patients (15 moderately dyslipidemic men) were given an oral fat load (OFL), and blood samples were collected before the OFL ingestion (T0) and 2, 4, 6, and 8 h (T2, T4, T6, T8) thereafter. Endothelial function, determined as flow-mediated dilatation (FMD) of the brachial artery, was assessed at the same time points. Triglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 44 publications
2
42
0
4
Order By: Relevance
“…Previous clinical studies have shown an acute and direct effect of hypertriglyceridemia on vascular endothelium. Acute hypertriglyceridemia induced by an oral fat load caused endothelial dysfunction in subjects with dyslipidemia 30 and increased circulatory cellular adhesion molecules in healthy subjects. 31 Further study is needed to clarify the involvement of apoCIII in this phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…Previous clinical studies have shown an acute and direct effect of hypertriglyceridemia on vascular endothelium. Acute hypertriglyceridemia induced by an oral fat load caused endothelial dysfunction in subjects with dyslipidemia 30 and increased circulatory cellular adhesion molecules in healthy subjects. 31 Further study is needed to clarify the involvement of apoCIII in this phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…The atherogenic effects of RLPs on the endothelium include upregulation of proinflammatory cytokines, monocyte recruitment and activation, and increased production of prothrombotic factors 4. Changes in RLPs in the postprandial state may lead to endothelial dysfunction as measured by flow‐mediated dilation 40. In an immunohistochemical analysis of carotid plaque after endarterectomy, RLPs were significantly associated with carotid plaque macrophage content, a surrogate for plaque instability 41.…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial hyperlipidemia has been also reported to be associated with insulin resistance syndrome and an effective indicator for developing vascular complications [15]. An abnormal postprandial elevation of TG or RLP has been suggested to lead to endothelial dysfunction [16]. Delayed clearance of postprandial large TG-rich particles is reported in subjects with LPL abnormality [17].…”
Section: Discussionmentioning
confidence: 99%